The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1063/1.322306
|View full text |Cite
|
Sign up to set email alerts
|

Double mass transfer during polymer-polymer contacts

Abstract: Double mass transfer has been observed spectroscopically and nondestructively for the first time using the x-ray photoemission technique to examine both halves of polymer films touched to other polymer films. A careful selection of polymers according to their peculiar x-ray photoemission spectra enabled the unambiguous identification of polymer fragments on the respective surfaces. The use of the nondestructive XPS or ESCA technique makes possible the observations involving both halves of the contacting pair, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 7 publications
0
49
0
1
Order By: Relevance
“…19,[58][59][60][61][62] It has been explained in terms of, for instance, charge-carrier diffusion along thermal gradients, 29 a suggestion that did not hold true in experiments. 59 For two polymers rubbed against each other, transfer of material in both directions has been observed, 63 and it has been suggested that charge might be transferred along with it. [9][10][11]25 The net charge on PTFE, generated by sliding metal contacts, has been found to be proportional to the square root of the load force, which in turn has been shown to be proportional to the contact area.…”
Section: B Related Literature Resultsmentioning
confidence: 99%
“…19,[58][59][60][61][62] It has been explained in terms of, for instance, charge-carrier diffusion along thermal gradients, 29 a suggestion that did not hold true in experiments. 59 For two polymers rubbed against each other, transfer of material in both directions has been observed, 63 and it has been suggested that charge might be transferred along with it. [9][10][11]25 The net charge on PTFE, generated by sliding metal contacts, has been found to be proportional to the square root of the load force, which in turn has been shown to be proportional to the contact area.…”
Section: B Related Literature Resultsmentioning
confidence: 99%
“…For example, when some polymers are rubbed with friction, an exchange of deeper layer materials occurs [52]. (This helps explain why even the same polymers can be charged by tribo-contacts; it is because even identical polymers will have different material compositions at each depth, which account for the same material charge transfer [29].)…”
Section: (Nano-) Materialsmentioning
confidence: 99%
“…In general, tribocharging is the process whereby a charge exists on a material after departing from the contact with a dissimilar material and the two materials can be any combination of conductor, semiconductor, or insulator (dielectric). Although it is thought that contact charging is the result of electron transferring from one body to the other (Rose-Innes, 1980), there is evidence in some cases that the charge transfer in contact charging can occur by ion transfer (Harper, 1967;Gaudin, 1971) and material transfer (Salanek et al, 1976). It is a common observation that the tribocharging process involves at least two physical mechanisms, which are equally vital in determining the determined by the work function parameters until the Fermi levels at the surface are equal.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…Material transfer in some cases (such as, when polymers and metals are brought into contact) is of possible notability to contact electrification, if the number of transferred atoms per unit area exceeds the charge density (in units of e per unit area) observed in the contact electrification (Lowell and Rose-Innes, 1980 (Salanek et al, 1976). With the use of ESCA for surface analysis, they showed that some of the metal transferred to the polymer and, likewise, some of the polymer to metal when they were in contact with each other.…”
Section: A) Materials Transfermentioning
confidence: 99%